Key Determinants of Rice Farming Profitability Among Smallholder Farmers in Kembaran District Indonesia - Malinda Aptika Rachmah; Budiyoko Budiyoko; Exwan Andiyan Verrysaputro (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
One of the main agricultural products in Banyumas Regency is still rice. Nonetheless, low profitability and farming efficiency result from most farmers in the area paying little attention to production input efficiency. This research aims to determine the factors influencing the income of rice farmers in the area and assess the profitability of rice farming in Kembaran District, Banyumas Regency. Fifty rice farmers were specifically chosen to participate in the study as respondents. The data was analyzed using the one-sample t-test, multiple linear regression, and profitability analysis. The findings indicate that rice cultivation in Kembaran District is financially feasible and generates a return greater than the 2.5% BRI deposit interest rate threshold, with an average profitability of 3.33%. Furthermore, regression analysis reveals that while the price of fertilizer and pesticide does not affect farmers' income, the price of labor and seed has a significant impact. These results suggest that rice cultivation in Kembaran District provides a higher rate of return than bank deposits. Farmers are advised to modify their production inputs to reduce expenses and increase revenue to maximize profitability further.